EXPLORING DIGITAL LITERACY, FINANCIAL LITERACY, AND SOCIAL MEDIA'S IMPACT ON CRYPTOCURRENCY INVESTMENT DECISIONS - Amran, Kevinia Mayumi; Adrianto, Fajri; Hamidi, Masyhuri (Universitas Muhammadiyah Gresik, 2025)
Social media and the digital era have had a big impact on investing decisions, particularly in the cryptocurrency space. This study investigates how social media, financial literacy, and digital literacy affect DKI Jakarta Millennials and Generation Z's decision-making when making investments. The study looks at the mental processes that underlie investing decisions and is based on theories of reasoned action and planned behavior. The study emphasizes how important financial literacy is for reducing risks and helping people make wise decisions. Digital literacy, on the other hand, improves one's capacity to navigate and evaluate large volumes of financial data. Social media is recognized as a key influencer that shapes public opinion and propels financial trends. The study's quantitative approach makes use of structural equation modelling (SEM) to examine data from an DKI Jakarta survey given to Millennials and Generation Z. The findings show that by improving access to and analysis of financial information, digital literacy has a positive impact on investment decisions. The study finds that making wise investment decisions in the cryptocurrency market requires a thorough understanding of social media, digital literacy, and financial literacy. Keywords: Digital Literacy, Financial Literacy, Social Media, Investment Decisions and Cryptocurrency.